Hepatitis E Infection in a Renal Transplant Recipient. (11th September 2014) - Vassallo, Diana; Husain, Mir Mubariz; Greer, Shaun; McGrath, Stephen; Ijaz, Samreen; Kanigicherla, Durga
Abstract : An asymptomatic 35-year-old renal transplant recipient was noted to have deranged liver function tests. Liver biopsy revealed a portal inflammatory process with mild lobular activity and portal fibrous expansion, consistent with a virally mediated process. An extensive viral screen confirmed infection with Hepatitis E virus genotype 3 (HEV-3). There is increased awareness about locally acquired Hepatitis E virus (HEV) infection in the transplant population in the UK. The important implications of this infection are becoming more apparent as progression to liver cirrhosis can occur. However, the incidence, natural history, and treatment of HEV infection in the transplant population are not well established. This report illustrates a case of delayed spontaneous clearance of the HEV infection.